Performance of double chamber microbial fuel cell: effect of waste water, electrode thickness and distance - Aziah Khamis; Nur Diana Nordin; Mohamad Hafiszi Mokhtar (Institute of Advanced Engineering and Science, 2020)
This paper presents the performance evaluation of a double chamber microbial fuel cell (MFC) to obtain the maximum amount of power production. Previous works have shown that the performance of a double chamber MFC varies depending on the design of the MFC and the type of waste water. Therefore, various MFC tests were conducted to obtain the maximum amount of power production by varying the distance of electrodes and thickness of the electrode. The types of water were also varied (i.e., fertilizer water, lake water, and soil water) to highlight the effect of the expected different amount of microbes. The experimental results demonstrated that the thicker anode (0.6 cm) and the shorter distances between electrodes (15 cm) showed higher amount of power production in all the three types of waste water. Furthermore, the fertilizer water generated a higher amount of power compared to the soil and lake water.